BORNOLOGICAL ON THE SPACE ALL ELEMINT REPRESENTED BY DIRICHLET SERIES (Journal of the College of Basic Education, 2022)
In this paper, we study and deal with the fundamental bornological constructions for bornology defines on the space of entire function all element represented by dirichlet series, such as bornological subspace, product bornologies and Quotient bornologies with adding some properties to them